KOMUNIKASI INTERPERSONAL ANTARA BIDAN DAN PASIEN IBU HAMIL DALAM PELAYANAN ANTENATAL CARE (ANC) DI PRAKTIK MANDIRI BIDAN (PMB) SRI WINARTI DESA SANGGRAHAN NGADIROJO - Pamungkas, Dewi; Hindra Hastuti, Nurnawati; Mahar Rizqi, Fikriana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Communication is a process of conveying messages carried out by one party and anotherparty with the aim of achieving mutual understanding of a message or information sent to eachother. Communication can occur anywhere including in the health sector. The purpose of thisstudy was to determine interpersonal communication between midwives and pregnant womenpatients in antenatal care (ANC) services at Sri Winarti's Independent Midwife Practice(PMB) Sanggrahan Ngadirojo Village. This research is based on the theory of interpersonalcommunication or interpersonal communication is a dialog communication that is establishedthrough a direct communication process between two or more people. Messages are received intwo directions, nonverbal and verbal, for example between midwives and patients. This type ofresearch is descriptive qualitative. The object of this research was conducted at PMB SriWinarti with informants of midwives and pregnant women patients. Data collection methodsused interviews, observation and documentation. Data analysis used qualitative analysis. Theresults of this study indicate that there is an interpersonal communication process carried outby midwives of pregnant women patients with 6 stages of interpersonal communication,namely the desire to communicate midwives with the intention of conveying messages.Encoding of the communicator, the use of words that are easy to understand and the use ofIndonesian and Javanese. Delivery of messages by midwives with verbal and nonverbalcommunication. Receiving messages that patients receive is done directly without media.Decoding from communicants, understanding the messages conveyed by midwives to patientsis understood and understood and understood. Feedback, patients provide feedbacak by askingfurther questions and nodding their heads.Keywords: interpersonal communication, Independent Midwife Practice (PMB), antenatalcare, midwives, pregnant women patients